2018
DOI: 10.5688/ajpe6189
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Community Pharmacy Simulation Program into a Therapeutics Course

Abstract: Objective. To demonstrate the feasibility of integrating the computer simulation, MyDispense, into a therapeutics course and to measure its effects on student perception and learning. Methods. We conducted a prospective study with an experimental phase and an implementation phase. In the first phase, students were randomized to complete a therapeutics case using MyDispense or traditional paper methods in class. In the second phase, all students completed two therapeutic cases using MyDispense in class with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…As technology becomes more ubiquitous throughout education, institutions of professional healthcare learning are incorporating various tools for students to utilize [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A 2011 survey of 89 pharmacy schools in the United States reported the use of some forms of technology ranging from lecture capture and presentation software to videoconferencing and social media.…”
Section: Introductionmentioning
confidence: 99%
“…As technology becomes more ubiquitous throughout education, institutions of professional healthcare learning are incorporating various tools for students to utilize [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A 2011 survey of 89 pharmacy schools in the United States reported the use of some forms of technology ranging from lecture capture and presentation software to videoconferencing and social media.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 19 - 21 For example, one study reported <30% of pharmacy students felt a computer simulation program was helpful for applying knowledge in a timely manner or developing a therapy plan, despite an improvement in student performance with more frequent use of the program. 20 Because this information seeking skill is a realistic feature of using electronic health records and because using electronic health records optimally is increasingly a skill needed by pharmacy graduates, 4 , 22 this is likely a frustration that should be discussed openly in case preparation and debriefing. Students should also be made aware that learning therapeutic reasoning within a realistic information gathering setting can promote stronger context-learning and therefore may better prepare students for pharmacy practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors continue to claim that MyDispense has a limited scope of simulation because it does not simulate hospital pharmacy practice or an authentic interaction with other health care providers and patients (low environmental fidelity). 22 However, given the aforementioned benefits of the MyDispense software, it could be incorporated within the current teaching approach to supplement and consolidate learning in a live dispensary session.…”
Section: Discussionmentioning
confidence: 99%